Hubungan Sistem Pengukuran Kinerja dengan Kinerja Manajerial: Peran Keadilan Prosedural, Kejelasan Peran, dan Komitmen Organisasi sebagai Variabel Pemediasi - Dasrita, Tuti; Rusli Tanjung, Amries; Mutia Basri, Yesi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2015)
Abstract The literature on performance measurement system indicates that the company should consider to increase the diversity of performance measures one of which is to merge/combine the size of the financial and non-financial performance. The purpose of this paper is to test whether the merge/combine size and non-financial performance can affect the performance of managerial finance. And how is the effect of the mediating role of procedural fairness, role clarity and organizational commitment in the relationship. Based on a sample of 103 bank managers of Bank in Riau, the study found that there was a significant relationship between performance measurement systems (financial and non-financial) and managerial performance are mediated by procedural fairness and organizational commitment. However, further analysis proved that the existence of a significant relationship between performance measurement systems (financial and non-financial) and managerial performance are mediated by role clarity.